Desain Primer dan Analisis in Silico untuk Amplifikasi Gen mt-Co1 pada Tikus got (Rattus norvegicus) - Maria A E D Sihotang; Yola Eka Erwinda; Eniek Suwarni; Erita Lusianti (Eruditio : Indonesia Journal of Food and Drug Safety, 2021)
Brown rat or commonly called sewer rat (Rattus norvegicus) meat is one of ingredients that is usually used to counterfeit beef meatballs to reduce the production prices. These issues can be very detrimental to consumers, in terms of health and halal reasons. Thus, this condition has prompted the development of test methods to detect sewer rat meat in processed foods. Several method developments in detecting the content of sewer rat meat in processed food have been carried out. One of the simplest and fastest methods to identify sewer rat meat is Polymerase Chain Reaction (PCR). Most method developments for detecting sewer rat meat have used endpoint PCR, but this method still has several shortcomings in terms of specificity and promptness in obtaining results. Therefore, developing a sewer rat meat detection method using real-time PCR and combined with a more sensitive and specific TaqMan probe can be an alternative for detecting sewer rat meat in processed foods. Primer and probe design is the first and crucial step in the development of detection methods with real-time PCR. This study aims to design primers and probes for the detection of the mt-CoI gene in sewer rats. The mt-CoI gene sequence of Rattus norvegicus (NC_001665.2) was obtained from the National Center of Biotechnology Information (NCBI) database. Primer was designed using Primer3Plus software. Then, several candidates of primers and probes were analyzed in silico for specificity of the mt-CoI gene using software, including Primer-BLAST and Nucleotide-BLAST. The result of this study is primers and probes which are specific to the mt-CoI gene in sewer rats (Rattus norvegicus), with the sequence of forward primer (5’-ATGAGCAAAAGCCC ACTTTG-3’), reverse primer (5’-CGGCCGTAAGTGAGATGAAT-3’), and probe (5’-GCAGGGATACCTCGTCGTTA-3’). The result can be used to develop methods for detecting sewer rat meat in meatballs or other processed foods using real-time PCR and TaqMan probes.